Persepsi Kualitas Sebagai Mediator Antara Merek, Desain, Harga dan Niat Beli Sepeda Motor - I Made Widya Suraputra; Ida Bagus Raka Suardana (Universitas Pendidikan Nasional, 2019)
ABSTRACTThis study examines the factors that influence purchase intention, with brand variables, design and price as independent variables and perceived quality as mediating variables. The purpose of this study is to find out how the influence of brand, design, price and quality perception on motorbike intention to buy in Denpasar City. Data collection techniques used were interviews, observation and questionnaires. The population used in this study is the people of Denpasar City. The number of samples taken was 100 respondents using the Non-Probability Sampling technique, namely accidental sampling. The data analysis technique used is the SEM analysis technique with the Partial Least Square (PLS) method and the SmartPLS 2.0 M3 program tool. The analysis results show that the purchase intention variable is influenced by brand variables, design and price, and the perception of quality as a mediating variable is also able to strengthen the influence of independent variables on the dependent variable. This study concluded that the brand, design and price directly and indirectly through perceived quality have a positive and significant effect on purchase intention. This research is useful for motorcycle manufacturers in the Denpasar City area to find out consumer behavior towards motorcycle products offered so that they can increase their sales. The limitations of variables and narrow areas will influence the results of the study, therefore further research can better complement these deficiencies.